Bridging the gap: public space as an anchor for social-infrastructure and community integration in Braamfontein - Kistan, Nicole (University of the Witwatersrand, Johannesburg, 2024)
Bridging the Gap is about creating a new shared space within Braamfontein, that seeks to provide a space that alleviates the interpreted apprehension felt towards shared spaces in the city. This tension that stems from the inaccessibility of space, infrastructure and amenities are due to the exclusionary nature of socio-economic hierarchies. The approach redefines the perceptions and physical role public space holds by investigating its history. Shared space, which is becoming increasingly scarce, is placed as a new gateway to the city to create a new and improved way of life. The design intervention combines architectural, urban, and social concerns by reinterpreting shared spaces as a social platform, which introduces a pedestrian street on ground level on which the architecture manifests as a flexible modular typology. The proposal aims to create an integrated and sustainable future in Braamfontein by engaging users, space and the city to create an urban fabric
A research report submitted in fulfillment of the requirements for the Masters in Architecture, In the Faculty of Engineering and the Built Environment, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; social-infrastructure; community integration; SDG-11: Sustainable cities and communities